Sosialisasi Penggunaan Internet sehat serta Gadget pada Anak Usia Dinidi Petukangan Selatan : Sosialisasi Penggunaan Internet sehat serta Gadget pada Anak Usia Dinidi Petukangan Selatan - Taufiq Ramadhan; Rika Handayani; Azmi Islami; Risnawati, Risna (Universitas Darunnajah, Jakarta, Indonesia, 2024)
Abstract. As technology evolves, it is very important for all of society to be able to manage usage wisely in order to maximize its benefits and minimize the risks it will incur. Gadgets are one of the visible forms of technological tools that are mostly used by the Society, which is always evolving from years of knowledge and can update new things so as to attract the interest of users. Not only parents or teenagers, but also early childhood and primary school children participate in this tool. Excessive use of gadgets will have a negative impact on development and growth in early childhood. This can happen and affect my behavior. In addition, excessive use of gadgets can affect the child and become a more closed person due to lack of social interaction with friends or relatives. However, the use of gadgets does not always have a negative impact, some of them use gadgets well and apply them as a learning medium that can be useful and bring insight. Therefore, they can easily access the Lessons online. However, the use of gadgets, especially in early childhood, requires periodic supervision of parents, because in early childhood they have a high sense of enthusiasm and curiosity about new things that they know that can lead to adverse risks, and can increase parents' concern with excessive use of gadgets by their children.